Identifying a baicalein-related prognostic signature contributes to prognosis prediction and tumor microenvironment of pancreatic cancer - Zhang, Citing; Lei, Defeng; Zhou, Yan; Zhong, Tongning; Li, Xuefei; Ai, Weipeng; Zheng, Biao; Liu, Jikui; Piao, Yicui; Yan, Zilong; Lai, Zhengquan (Frontiers in Immunology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most malignant and lethal human cancers in the world due to its high metastatic potential, and patients with PDAC have a poor prognosis, yet quite little is understood regarding the underlying biological mechanisms of its high metastatic capacity. Baicalein has a dramatic anti-tumor function in the treatment of different types of cancer. However, the therapeutic effects of baicalein on human PDAC and its mechanisms of action have not been extensively understood. In order to explore the biological characteristic, molecular mechanisms, and potential clinical value of baicalein in inhibiting the metastatic capacity of PDAC. We performed several in vitro, in vivo, and in silico studies. We first examined the potential regulation of baicalein in the metastatic capacity of PDAC cells. We showed that baicalein could dramatically suppress liver metastasis of PDAC cells with highly metastatic potential in mice model. The high-throughput sequencing analysis was employed to explore the biological roles of baicalein in PDAC cells. We found that baicalein might be involved in the infiltration of Cancer-Associated Fibroblasts (CAF) in PDAC. Moreover, a baicalein-related risk model and a lncRNA-related model were built by Cox analysis according to the data set of PDAC from TCGA database which suggested a clinical value of baicalein. Finally, we revealed a potential downstream target of baicalein in PDAC, we proposed that baicalein might contribute to the infiltration of CAF via FGFBP1. Thus, we uncovered a novel role for baicalein in regulation of PDAC liver metastasis that may contribute to its anti-cancer effect. We proposed that baicalein might suppress PDAC liver metastasis via regulation of FGFBP1-mediated CAF infiltration. Our results provide a new perspective on clinical utility of baicalein and open new avenues for the inhibition of liver-metastasis of PDAC.